Pengaruh Tingkat Pemahaman dan Kesadaran Pedagang Terhadap Minat Membayar Zakat Perdagangan di Kecamatan Gerung - Arif Rahman Hakim; Ahmad Amir Aziz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research was motivated by problems that occurred related to the lack of public understanding and awareness of paying trade zakat. Zakat is a worship that can be used to overcome social problems so awareness and understanding are needed in paying trade zakat. This study aims to determine the influence of the level of understanding and awareness of traders on the interest in paying trading zakat. This type of research uses causal associative research with data collection methods using observation methods and questionnaires. Sampling in this study used non-probability sampling techniques by purposive sampling with a total of 95 trader respondents in the Gerung District. The data analysis technique used was multiple linear regression using the IBM 26 version of SPSS. The results showed that: (1) the level of understanding had a positive and significant effect on the interest in paying zakat trading (2) the awareness of traders had a positive and significant effect on the interest in paying zakat trading (3) the level of understanding and awareness of traders had a simultaneous effect on the interest in paying zakat trading.